1997
DOI: 10.1177/1359104597021009
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Representation Reassessed

Abstract: This article reports the possible clinical implications of an empirical examination of mental representations, in particular that of maternal representations before and after the birth of a first child. The study investigates maternal representations including the mental organization of perceptions, thoughts and feelings of priminparous women during the third trimester (seventh month) of pregnancy and four months postbirth. We focus on the representations that a woman has of herself, her baby, of her partner, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Results showed that size of social support network was the strongest predictor of prenatal RF. The availability of social support appears to benefit the adjustment to upcoming motherhood (Sadler et al., ; Smith, ), resulting in stable perceptions of the future infant in the last trimester of pregnancy (Larney et al., ). Feeling supported facilitates women to gain confidence in the new perceptions of themselves and eases the transition into motherhood (Darvill et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results showed that size of social support network was the strongest predictor of prenatal RF. The availability of social support appears to benefit the adjustment to upcoming motherhood (Sadler et al., ; Smith, ), resulting in stable perceptions of the future infant in the last trimester of pregnancy (Larney et al., ). Feeling supported facilitates women to gain confidence in the new perceptions of themselves and eases the transition into motherhood (Darvill et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…These factors could affect prenatal maternal RF. Maternal characteristics that have been negatively related to RF include psychiatric illness (Fonagy & Luyten, ; Levinson & Fonagy, ; Perry, Newman, Hunter, & Dunlop, ; Toth, Rogosch, & Cicchetti, ), substance use during pregnancy (Pajulo et al., ), single parenthood (Huth‐Bocks, Levendosky, Bogat, & Von Eye, ), unavailability of support from family and friends (Larney, Cousens, & Nunn, ; Sadler et al., ; Smith, ), scarcity of material resources (e.g., regarding housing or financially), and low educational attainment (Pajulo, Helenius, & Mayes, ; Rosenblum, McDonough, Sameroff, & Muzik, ; Sadler et al., ; Theran et al., ; Vrieze, ). These factors also have been used to define risk status with respect to child sociobehavioral outcomes (World Health Organization, ).…”
mentioning
confidence: 99%
“…Maternal representations are one important mediating pathway between a mother's personal history, especially of her childhood experiences, and her interactive behavior with the infant. Representations are mental constructions of reality based upon memories, expectations, and perceptions that guide both one's sense of self and interpersonal behavior (Larney, Cousens, & Nunn, 1997; Main, Kaplan, & Cassidy, 1985). During the transition to parenthood, the major representational domains involve the child, the self‐as‐mother, the self‐as‐woman, one's own mother‐as‐mother and the child's father (L. Cohen & Slade, 2000; Fava Vizziello, Antonioli, Cocci, & Invernizzi, 1993; Stern, 1995).…”
Section: Role Of Maternal Representationsmentioning
confidence: 99%
“…Representations of the self, the child, the child's father, and one's own mother tend to remain quite stable from the prenatal to the postnatal period, and such stability has been found both among normative (Flykt et al, 2009; Larney et al, 1997; Stern, 1995) and psychosocial‐risk mothers (Theran, Levondosky, Bogat, & Huth‐Bocks, 2005; Wendland & Miljkovitch, 2003). If representational change occurs (i.e., prenatal representations do not match postnatal reality), the change appears to be in a positive direction (Flykt et al, 2009; Larney et al, 1997); however, we do not know whether these results apply specifically to drug‐abusing mothers.…”
Section: Role Of Maternal Representationsmentioning
confidence: 99%
“…By stimulating early unconscious memories, the group provides material and experiences for new internal representations (Larney et al, 1997). Experiences with the therapists make it possible for the mothers to attempt to repair negative representations of their own mothers.…”
Section: Preventing Negative Projections Onto the Infantmentioning
confidence: 99%